The Urgency Of Coaching Education Unit Supervisors In Improving Quality - Nurwafika, Nurwafika; Nur, Faizal; Misbah, Nurlaelah; A, Arisal (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
Providing education unit supervisors is carried out by researchers at SMK Negeri 7 Bone that in management has been carried out properly, with this the school management process can be said to have been implemented or is optimal, but in these schools sometimes the management process still needs to be developed due to several obstacles. faced by the education supervisory unit in improving the quality of Madrasah management. The purpose of this study is to find out how the supervision of educational units in SMK Negeri 7 Bone and to find out how the quality of management in SMK Negeri 7 Bone. The type of research conducted here is descriptive research with qualitative methods of observation, interviews, and documentation.